Sokolský exil jako přirozený důsledek podstaty sokolství [Sokol exile as a real consequence of the Sokol essence] - Bohuslav Hodaň (Palacký University Olomouc, 2008)
Letošní rok je jubilejním devadesátým rokem založení Československé republiky. Je to doba, kdy je vhodné vzpomenout událostí, které jsou historicky významné. Patří mezi ně i exilové hnutí, které je spojeno s několika etapami tohoto vývoje. Významnou součástí exilového hnutí byl i sokolský exil, do kterého se zapojilo velké množství členů Sokola. Nebyla to náhoda, ale logické vyústění sokolské "ideologie", logické vyústění filozofie, na jejímž základě sokolská organizace díky Tyršovi vznikla. Práce se vrací k jednotlivým etapám sokolského exilu a ukazuje vzájemnou propojenost sokolství - vlastenectví - brannost - exil. Zdůvodňuje také, proč se zabývá pouze obdobím do roku 1950. [The year 2008 is the year of the ninetieth anniversary of birth of the Czech-Slovak Republic. Since then, our state passed a very complicated and difficult development. In reaction on political events, many individuals, organizations and various movements participated on the birth and development of this state. One of these very important phenomena was the Czech-Slovak exile movement and its representative part, the exile of Sokol. In this movement, thousands of Sokol members participated. The connection of Sokol and the exile was not caused by chance or was not a result of an "ad hoc" solved situation. In all periods it was a logical consequence of content and realization of thoughts of the system, which the Sokol was bearer of. The exile activities, aversion against any non-democratic, anti-humanistic or even totalitarian tendencies were simply automatic and self-evident consequences of the Sokol "ideology" witnessed numerous changes of the political setting and underwent some changes in its own development. So, the ideology and the corresponding education were the basic presumptions of Sokol exile, manifested in the political, humanitarian as well as military sphere. The Sokol exile is not an exceptional part of Sokol history, because it logically grows up from these presumptions: direction of Sokol system to raising of all-round human level, direction of Sokol system to the human responsibility for himself and society, direction of Sokol system to education to engaged citizenship, direction of Sokol system to the improvement of Czech (Czech-Slovak) society and ability of its defence. The Sokol exile activities are connected with the names of T. G. Masaryk, Jan Masaryk, Edvard Beneš and others. They were implemented in these periods: before and during the first world war, before and during the second world war, after 1948 and after 1968. For insufficiency of sources the exile after 1968 is not included in this article.]